Effects of a regional–rural immersion program in Northland, New Zealand, on returning to work in that region. (14th May 2022) - Connell, Charlotte J. W.; Bagg, Warwick; Jo, Emmanuel; Poole, Phillippa
Abstract: Introduction: It is well established that rural workforce outcomes are more likely among medical graduates who spend time training in non‐urban areas; however, fewer studies have assessed whether graduates are more likely to return to the specific area where they undertook rural training. Objective: This study aimed to determine whether graduates who had undertaken a regional–rural immersion program in Northland, NZ, were more likely to have returned to work in Northland as of mid‐2021, relative to peers who did not participate. Design: This prospective cohort study used longitudinal tracking survey responses, medical school administrative data and workforce outcome information. A multinomial model, accounting for other covariates, was built to determine the association between graduates practising in Northland (population ⟨ 100 000), which encompasses both rural (population ⟨ 25 000) and regional (25 000 ⟩ population ⟨ 100 000) areas, and having participated in a Northland‐based immersion program during medical school. The study population was University of Auckland domestic medical students graduating between 2009 and 2018, inclusive. Immersion program participants who responded to longitudinal career tracking surveys were included in the study sample. Findings: The final sample size was 1320 students (80% of population of interest). Graduates who undertook the Northland immersion program ( n = 169) were more likely than non‐participants ( n = 1151) to be working in Northland as of 2020–2021 (relative risk: 3.2). Discussion and Conclusion: Regional–rural immersion programs might preferentially build workforces in that specific region; however, further research is required to understand whether these findings are generalizable, and the main reasons for this effect.